PENETAPAN HARGA PADA PASAR OLIGOPOLI - Indah Ayu Rahmawati (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
Oligopoly is a market where supply one type of goods controlled by a few companies. Oligopoly is usually done as an effort to hold companies to enter the market, and the purpose of doing oligopolistic firms is as an attempt to enjoy a profit by the sale price is limited, resulting in price competition among businesses that do oligopolistic practices become nonexistent. Pricing (price fixing) in Islam is not allowed because it would cause a rise in prices due to competition and the free market will also lead to a shortage of production when the demand is a lot or ride, which eventually will lead to shortages of goods. However, in order to maintain fairness between producer and consumer, the government has the right to menetakan price. In setting prices, the government should think about the benefit of traders and consumers in order not to feel aggrieved.